Computation of structural parameters developed by shot peening and their influence on residual stress and wear properties of AA2017 alloy - Venumurali, Jagannati; Turaka, Seshaiah; SanthaRao, Dakarapu; Krishnan, Pradeep Kumar; Tirumala, Tumula; Ravindra, Kurra; Rajesh, Krishna; Pappula, Bridjesh; Makgato, Seshibe (Journal of alloys and compounds, 2025)
AA2017 aluminium alloy, widely used in aerospace and automotive due to its strength-to-weight ratio and corrosion resistance, faces challenges in optimal mechanical performance due to its inherent surface brittleness. This study quantitatively investigates the structural and mechanical enhancements induced by Shot Peening (SP) in AA2017, employing a comparative approach with as-received (AR) samples. Crystallographic parameters were derived via X-ray Diffraction Line Profile Analysis (XRD-LPA) using the Pseudo-Voigt fitting method to evaluate changes in crystallite size, micro-strain, and dislocation density. SP treatment led to a significant grain refinement, with crystallite size reducing from ∼168 nm (AR) to ∼41 nm shot peened (SPed), a 75 % reduction. Micro-strain increased from 0.0182 to 0.0315, and dislocation density increased from 1.73 × 10 ¹ ⁴ m⁻² to 6.21 × 10 ¹ ⁴ m⁻², confirming intense plastic deformation. Compressive residual stresses were confirmed using the Cos α method, correlating with a 230 % increase in surface microhardness (from 71 ± 2 HV to 235 ± 7 HV). Wear resistance improved substantially, with a 35 % reduction in wear rate (from 1.046 ± 0.002 mm³/KN-m to 0.776 ± 0.0018 mm³/KN-m), and the coefficient of friction decreased by 11 %. SEM and optical microscopy revealed a gradient structure in SPed samples, characterised by refined grains near the surface and coarse grains beneath, absent in AR samples. These improvements surpass similar enhancements reported in AA2024 and AA7075, where maximum microhardness gains were ∼180–200 % under comparable SP conditions. This study addresses the knowledge gap on SP treatment in copper-rich, low-ductility aluminium alloys, offering a robust methodology for enhancing surface modification strategies for high-performance applications. •The structural and mechanical modifications in AA2017 alloy induced by shot peening was investigated.•Shot peening reduced crystallite size in AA2017 by ∼75 %, enhancing microstructure.•Dislocation density and micro-strain increased, confirming intense plastic deformation.•Compressive residual stress induced a 230 % rise in surface microhardness.•Wear rate dropped by 35 % and friction coefficient fell by 11 % post shot peening.